Child Maltreatment Severity Questionnaire (MSQ) for professionals: development, validity, and reliability evidence - Calheiros, M. M.; Silva, C. S.; Magalhães, E. (Assessment, 2021)
This article presents the development and validation of the child Maltreatment Severity Questionnaire (MSQ), aiming to contribute to increase the quality and efficiency of evaluation processes in the Child Protection System (CPS). To obtain a valid and reliable instrument, a set of studies was developed: Study 1—Based on two previous studies, the questionnaire was developed and the severity level of the items within maltreatment subtypes was assigned by 93 professionals from the welfare and CPS system. Consensus about the severity levels was assessed and described in terms of within-item reliability rankings; Study 2—The MSQ was filled out for 253 children and adolescents referred to the CPS. To ensure that the items within different subtypes of maltreatment were homogenous and had internal consistency, a reliability analysis was performed; Study 3—The MSQ was filled out for 1,000 children and adolescents referred to the CPS. This study involved testing validity evidence through an exploratory and a confirmatory factor analysis. We also analyzed the internal consistency, sensibility (i.e., sex and age differences) and concurrent validity of the MSQ. Findings support the adequacy and reliability of the MSQ to be used by CPS professionals in evaluating child maltreatment.